Entendesse?, Sabe? e Visse? como marcadores discursivos na fala de Pelotas/RS - Messa, Gedeon Eloeno Rodrigues (2013)
This work aims to analyze and describe the variation of Discourse Markers derived from verbs entender (to understand), saber (to know) and ver (to see) in different social classes upper-middle class and lower class considering speeches of informants from Social Class Sociolinguistic Database (VarX) based on Labov s theory of Linguistic Variation and Textual-Interactive Perspective. From the bibliographic literature of this search the items entender (to understand), saber (to know) and ver (to see) are considered Interaction s Discourse Markers. In view of the few existing data, linguistic and social variables do not contribute significantly to variation these Interaction s discourse markers, nor for the variation in relation to the agreement of the item entender (to understand) (because it was the only item that suffered variation in verbal form). The results only indicate some evidence that it will go to meet other sociolinguistic studies. Thus, the work focused on a more qualitative analysis of the data; however, the study contributes to a better understanding of linguistics phenomena that marks language in use in thelinguistic community of Pelotas.